Calculation of Cost of Goods Sold and Preparation of Income Statement at MSME Dapur Mamak - Rini Tri Hastuti; Tanya Edwina Abigail; Gracia Agatha Widjaja; Julianty Threevani (Transpublika Publisher, 2025)
Backgrounds: The rapid expansion of SME-scale restaurants, driven by social media culinary reviews, highlights the growing need for effective financial management in small business operations. Despite their increasing presence, many SME owners lack awareness of proper accounting practices and their impact on business sustainability. Dapur Mamak, an SME-scale restaurant established in 2023 and operating in the canteen of Tarumanagara University 2, West Jakarta, illustrates this condition. The business currently determines selling prices based on rough estimates and does not maintain formal bookkeeping. Objectives: This community service initiative was conducted to assist in designing a feasible food court model from marketing and management perspectives, strengthen MSME capacity in branding, promotion, and operational management, and build collaborative community involvement to support the establishment of a sustainable culinary centre. Methodology: The implementation methods included initial observation, MSME needs mapping, focus group discussions, marketing strategy mentoring, tenant management training, and the development of a comprehensive food court blueprint. Findings: The results indicate that the food court initiative provides an effective strategic solution for MSMEs by offering a representative business location, increasing collective brand visibility, and enabling marketing synergy among tenants. Conclusions: The community-based food court demonstrates strong potential as a sustainable MSME marketing hub. To ensure long-term sustainability, the programme should be further developed through partnership schemes, community-based branding, and collaborative village business models.